The impact of modifiable factors on image quality of prostate magnetic resonance imaging and PI-RADS scores - Lambert, Lukas; Macova, Iva; Wagnerova, Monika; Jurka, Martin; Burgetova, Romana; Capoun, Otakar; Burgetova, Andrea (Quantitative imaging in medicine and surgery, 2025)
BACKGROUND: The diagnostic accuracy of prostate magnetic resonance imaging (MRI) is highly dependent on image quality. Although the effects of spasmolytics and rectal preparation have been previously studied, the findings remain inconsistent and fail to address other critical modifiable factors. This study aimed to evaluate the impact of various modifiable factors on prostate MRI image quality and their subsequent influence on Prostate Imaging Reporting and Data System (PI-RADS) scoring. METHODS: Fifty-six consecutive patients who underwent 3T multiparametric MRI (mpMRI) with the administration of hyoscine butylbromide (HB+) and at least one 3T mpMRI without HB (HB-) ≤3 years earlier were retrospectively evaluated. Two radiologists performed morphometry of the prostate, bladder, rectum, and abdomen and evaluated image quality, artifacts, and motion on a five-point scale and T2 and diffusion-weighted imaging (DWI) PI-RADS v2.1 scores. The influence of HB, rectum and bladder distension, breathing motion, and examination hour were analyzed. RESULTS: The sharpness and overall image quality of T2 images were significantly better in HB+ compared to HB- (P=0.0047 and P=0.013). T2 motion artifacts were reduced earlier in the day (ρ=0.32, P=0.017). DWI susceptibility artifact correlated with patient diameter (ρ=0.40, P=0.002), but not with rectum diameter (ρ=0.09, P=0.51) or gas content (ρ=0.13, P=0.33). Examinations later in the day were associated with increased motion artifacts on T2 [hazard ratio (HR) =1.36]. T2 and DWI scores were influenced by bladder volume, breathing motion, and rectal air, but not by HB. Breathing motion negatively impacted overall image quality (HR =1.24), and DWI susceptibility artifacts (HR =1.22). CONCLUSIONS: HB administration, daytime, and breathing motion have significant influence on image quality of prostate MRI. The gas content of the rectum influences T2 image quality and T2 scores. Bladder filling is associated with reduced breathing motion, subsequently affecting DWI scores.